The Risk Assessment of Multi Hazard Area: A Case of Mitigation Consider in Spatial Planning of Bukittinggi City - Firmansyah Firmansyah; Deden Syarifudin; Jajan Rohjan (Faculty of Geography, Universitas Gadjah Mada, 2019)
The city of Bukittinggi in West Sumatra Province is geographically prone to multi hazard. The located along the active fault line of Sumatra namely Ngarai Sianok that shifted eleven centimeters per year, which is surrounded by two volcanoes, namely Mount Singgalang and Mount Marapi. Looking at the potential of multihazard disasters, this study aims to analyze the multi-disaster that is the input for development policy. The method used to assess factors with Davidson standardization model and superimpose. To obtain the level of importance of disaster risk factors used weighting by using analytical hierarchy process method by expert judgement. The study results show areas at high risk for earthquake, landslide, fire and flood disasters and disaster mitigation measures to reduce risks to hazard, vulnerability and resilience factors. Contribution in this reseach that spatial multi-hazard consideration should be undertaken as a consideration of development policies in order to reduce disaster risk.